Conocimiento y cuidados ante reacciones postvacunación en madres de menores de 1 año de la IPRESS I-4 Bellavista Nanay Iquitos 2024 - Velasquez Ramirez, Yasira Abigail (2025)
The objective was to determine the relationship between knowledge and care in the event of post-vaccination reactions in mothers with children under 1 year of age, at the IPRESS I-4 Bellavista Nanay, Iquitos 2024. Quantitative, observational, descriptive, cross-sectional and correlational study; The population was made up of 45 mothers. The survey and home visit were used as a technique; Instruments: a questionnaire on knowledge about post vaccination reactions and a questionnaire on care for post-vaccination reactions (validity 89.17% and 89.58%) and (reliability 80.01% and 82.95%).The results obtained were: 64.4% of mothers had low knowledge of post-vaccination reactions (local and systemic), 35.6% medium and 0.0% high; 51.1% of mothers presented inadequate care for post-vaccination reactions and 48.9% adequate. Regarding care for local post-vaccination reactions in mothers, 86.7% do not provide care to their child for pain in the applied area, and the same figure when they present redness in the area and 66.7% do not provide care when they have hardening in the area where the vaccine was applied; while in care for systemic reactions, 71.1% do not provide care for their child when they have irritability after vaccination. When relating knowledge with care for post-vaccination reactions, an X2c = 6.774 df = 1 p = 0.009 < α = 0.05 was obtained; indicating statistical significance between both variables. Concluding that low knowledge is related to the inadequate care of mothers of children under 1 year of age, in the face of post vaccination reactions.